EiA’s long-term experiments (LTEs) for assessing long-term sustainability and climate change adaptation - Saito, Kazuki; Casimero, Madonna; Rosenstock, Todd S.; Six, J.; Snapp, S.; Chikowo, Regis; Vanlauwe, Bernard (2023)
Long term experiments (LTEs) are critical in relation to the slow variables of the agronomic gain key performance indicators (KPIs) related to sustainability, including aspects of productivity and environment. The CGIAR Centers involvedin Excellence in Agronomy Initiative (EiA) are managing 32 LETs, ranging from 7 to 61 years old. These experiments that are on maize, rice, and wheat based cropping systems, are located in East and Southern Africa (15), Latin America (6) South Asia (4), and few in Central and West Asia and North Africa, Southeast Asia, and West and Central Africa. This report describes the importance of LTEs, provides an inventory of LTEs managed by the CGIAR Centers and details, and describes the EiA’s plan to initiate activities for the development of the next generation of LTEs.